P7. Early parietofrontal network upregulation relate to subsequent limited recovery after a severe motor stroke. Issue 8 (August 2021) - Backhaus, W.; Braaß, H.; Higgen, F.; Gerloff, C.; Schulz, R.
Abstract : Recent brain imaging has evidenced that parietofrontal networks show alterations after stroke which also relate to the motor recovery processes. There is converging evidence for an upregulation of parietofrontal coupling between parietal brain regions and frontal motor cortices. The majority of studies base these findings on moderately to mildly affected patients particularly in the subacute or chronic stage. Whether these network alterations will also be present in severely affected patients and early after stroke and whether such information can be used to improve correlative models to infer motor recovery remains unclear. Nineteen severely affected first-ever stroke patients (mean age 74 years, 12 females) underwent resting-state functional MRI and clinical testing during the initial week after the event. Clinical evaluation was repeated after three and six months. Nineteen healthy participants of similar age and gender were also recruited. MRI data were used to calculate functional connectivity values between the ipsilesional primary motor cortex, the ventral premotor cortex, the supplementary motor area and the anterior and caudal intraparietal sulcus of the ipsilesional hemisphere. Linear regression models were estimated to compare parietofrontal functional connectivity between stroke patients and healthy controls and to relate them to motor recovery. The main finding was a significant increase in ipsilesional parietofrontal coupling between anterior intraparietal sulcus and the primary motor cortex in severely affected stroke patients ( P  < 0.003). This upregulation significantly contributed to correlative models explaining variability in subsequent motor recovery: Patients with increased parietofrontal coupling in the acute stage showed higher levels of disability and residual motor impairment in the late subacute stage of recovery ( P  < 0.05). This study provides novel insights that parietofrontal networks of the ipsilesional hemisphere undergo neuroplastic alteration already very early after severe motor stroke. The association between early parietofrontal upregulation and future levels of persistent functional deficits and dependence from help in daily living might be useful in models to enhance clinical neurorehabilitative decision making.